Product Development in Dish Wash Cake Manufacturing Industry Using Project Management - Rozinadane, D (Digital Repository of Theses, 2025)
More recently during and after the coronavirus pandemic, there was a sudden increase in the demand for soap items, sanitizers, masks, medicines, and so on. There was a great struggle in the industrial sectors to meet the balance between the increased demand and supply of soaps, masks, and even vaccines. The research question is that during similar crises whether production in an industry could be increased rapidly by using project management techniques to solve crises. The present research is an attempt in this direction. This study was conducted in the dish wash soap manufacturing industry. In the present study, project management techniques were adopted to increase the production of dish wash soaps. After a thorough analysis of the manufacturing process of the soaps, seven important viable locations were identified in the existing mechanical system to make modifications and increase production. Consequently, some modifications were also made in human resources. The total production and other associated factors like quality, electrical power consumption, breakdown time and frequency, and excess giveaway were assessed before and after the modifications in a random sample of 33 shifts in nine months and compared. Statistical techniques, such as mean, standard deviation, and ANOVA were employed to analyze the data. The results showed that there was no change in the quality of the soap cake and electric power consumption after the modifications. The bulk manufacturing time, breakdown time, and frequency were reduced. The production of soap cake was increased considerably by 12.63%. More importantly, the result showed that the excess giveaway was reduced considerably. On the whole, the project management was a grand success in increasing in production of soap cake.